Análisis de la carga eléctrica a instalarse para el diseño del sistema eléctrico de la nueva planta RVR transformadores CIA. LTDA. de la ciudad de Quito - Rubio Faz, Edwin Oswaldo (2016)
The industrial sector has had a significant growth demand of electric energy focused a productive growth depending on consumption and electric supply to the equipment for a correct functioning. This project presents a study of design of an electric system measurement to the new RVR plant, which will help to supply of energy to the charges to be installed. First the electrical charge requirements analyzes as power, voltage to obtain the parameters of dimension of the transformer, taking as base on consumption of the electric equipment, and applying the design guidelines of the EEQ. The result were simulated in the informatic support ATAP 12.6.0 which helped to determine the behavior of the system under normal operating conditions, with the charge Flow Analisys application, it was possible to perform charge balancing at all points of installations. For calculating of the lighting dimension it has been made through the luminic study of the different places of placement that was used the informatics support DIAlux 4.12 with which was determined the lighting according to the rules NEC-10, and levels of lighting of the rule UNE-EN 12464-1, kinds of control of lighting to obtain an appropriate use of the energy.